The Role of Technology in Knowing Intellectual Intelligence in Elementary School Children - Abdul Rasyid; Him Patry (International Journal of Language and Ubiquitous Learning, 2024)
Background. The use of technology has positive and negative impacts depending on the ability of users, especially children to use it. The policy of using technology has a significant impact on the development of children's brain abilities, this also affects the level of children's intelligence. It is the responsibility of parents to know the changes that occur during the child's growth and development. Purpose. This study aims to evaluate the extent of the influence of technology on children's intellectual intelligence, especially in elementary school children. The focus of this research is to understand how technology affects the intellectual development of children in this age group. Method. The approach used in this study is a quantitative method. Data was collected through the distribution of questionnaires using Google Forms, which were filled out by teachers in elementary schools. This approach allows for the collection of relevant data directly from those who interact with children in the context of daily education. Results. The results of the study show that the use of technology has a double impact, namely positive and negative, on the intellectual intelligence of elementary school students. Technology can improve skills and knowledge if used appropriately. However, without adequate supervision, technology can also have negative impacts, such as decreased concentration and unbalanced social development. Conclusion. The conclusion of this study explains that technology is able to have a positive impact on students' intellectual intelligence if under the proper supervision of parents. If parents are negligent in controlling technology for children, it will have negative and fatal consequences.